Inteligência artificial e humanismo de fraternidade - Carbajo-Núñez, Martín (Revista Eclesiástica Brasileira, 2024)
Este artigo apresenta algumas “fascinantes oportunidades e [alguns] graves riscos” da inteligência artificial (IA) à luz do recente magistério do Papa Francisco. Não é uma tarefa fácil, pois o temo “inteligência artificial” se refere a uma “galáxia de realidades” e não há uma definição unívoca dela. Recentemente, com a IA criativa (1ª parte) houve um salto qualitativo. Seus desafios devem ser abordados a nível legislativo e ético (2ª parte). Mais concretamente, o Papa insta a adotar um humanismo de fraternidade inspirado em Francisco de Assis (3ª parte). Abstract: This article presents some of the “exciting opportunities and grave risks” of artificial intelligence (AI) in light of the recent magisterium of Pope Francis. This is not an easy task, as the term “artificial intelligence” refers to a “galaxy of different realities” and there is not a single definition of it. Recently there has been a qualitive leap with generative AI (1st part). Its challenges must be addressed at the legislative and ethical levels (2nd part). More specifically, the Pope urges the adoption of a humanism of fraternity inspired by Francis of Assisi (3rd part). Keywords: Artificial intelligence; ChatGPT; Pope Francis; Franciscanism; Ethics.